1984
DOI: 10.1007/bf00177895
|View full text |Cite
|
Sign up to set email alerts
|

Primary central nervous system tumors in stillborns and infants

Abstract: An epidemiologic investigation of true neoplasms of the central nervous system in fetuses and infants in the German Democratic Republic (GDR) was undertaken. Since all fetal deaths and all deaths in the first year of life are subject to a full postmortem examination and since all cancer cases or deaths are reported to a central registry, the prerequisites for a valid assessment of the incidence of these tumors are present. During the years 1960-1979, 55 histopathologically verified tumors of the central nervou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…In 1973, Jellinger and Sunder-Plassmann [2] proposed the following classification of congenital brain tumors: definitely congenital, presentation at birth or within 2 weeks of life; probably congenital, within 1 year of life; and possibly congenital, beyond 1 year of life. Various pediatric series have consistently reported grade I–III astrocytomas as the second most common intracranial congenital neoplasms, following medulloblastoma, teratomas or primitive neuroectodermal tumors [1, 3]. Glioblastoma, in contrast, is extremely rare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1973, Jellinger and Sunder-Plassmann [2] proposed the following classification of congenital brain tumors: definitely congenital, presentation at birth or within 2 weeks of life; probably congenital, within 1 year of life; and possibly congenital, beyond 1 year of life. Various pediatric series have consistently reported grade I–III astrocytomas as the second most common intracranial congenital neoplasms, following medulloblastoma, teratomas or primitive neuroectodermal tumors [1, 3]. Glioblastoma, in contrast, is extremely rare.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital primary brain tumors are rare and carry an estimated incidence of 1.1–3.6 per 100,000 newborns [1]. In 1973, Jellinger and Sunder-Plassmann [2] proposed the following classification of congenital brain tumors: definitely congenital, presentation at birth or within 2 weeks of life; probably congenital, within 1 year of life; and possibly congenital, beyond 1 year of life.…”
Section: Discussionmentioning
confidence: 99%
“…1 Congenital brain tumors are rare, with an incidence of 3.6 to 4.1 per 100 000 births. [2][3][4] There are no consensus definitions for "congenital" brain tumors. Jellinger and Sunder-Plassmann 5 proposed a classification system for definitions of "congenital": definitely congenital, producing symptoms at birth or within the first 2 weeks of life; probably congenital, producing symptoms in the first year of life; and possibly congenital, producing symptoms beyond the first year of life.…”
Section: Anaplastic Astrocytomas and Glioblastomas (World Healthmentioning
confidence: 99%
“…Brain tumors occur ring in children under 2 years are more common than usually thought and differ in location, histology, and out come from tumors occurring in older children [ 1 -8] eral large series have found that 11-16% of childhood brain tumors occur in children less than 2 years of age [1][2][3][4], Supratentorial tumors predominate in younger children. A Scandinavian study of deaths in the first year of life, including stillborn deliveries, revealed the inci dence of brain tumors to be 1.1/100.000 births [9], The incidence of brain tumors in children under 16 years of age is generally accepted to be 2 -3 /100.000. which sug gests that many tumors develop early in life [10], Al though the same spectrum of pathology occurs in infants and older children, infants have a disproportionately large incidence of chiasmatic-hypothalamic gliomas (CHG), choroid plexus tumors, and malignant congenital or embryonal tumors.…”
Section: Introductionmentioning
confidence: 99%